Hepatocyte-derived Microparticles as Novel Biomarkers for the Diagnosis of Deep Venous Thrombosis in Trauma Patients - Zang, Xinwei; Su, Yu; Zhang, Wenjie; Cao, Xiangyu; Li, Chunyan; Lu, Shan; Zhao, Huiru; Chen, Yuying; Liang, Cuiying; Wu, Jun (Clinical and applied thrombosis/hemostasis, 2023)
Venous thromboembolism is a common complication following trauma. We investigated the dynamics of plasma microparticles (MPs) levels and explored their potential as biomarkers of deep vein thromboembolism (DVT) after trauma. A total of 775 patients with traumatic fractures were recruited in this nested study. About 106 trauma patients (53 DVT subjects and 53 age-, sex-, and fracture site-matched non-DVT subjects) and 53 healthy volunteers met the enrollment criteria. MPs were characterized by transmission electron microscope, nanoparticle tracking analysis, and western blotting. Circulating levels of MPs were measured using a flow cytometer. Meanwhile, routine laboratory parameters were examined in all patients. Compared to non-DVT patients, DVT patients had higher circulating phosphatidylserine (PS) + MPs, hepatocyte-derived MPs (HMPs), PS + HMPs, and platelet-derived MPs (PMPs). Notably, PS + HMPs had the best predictive value for DVT diagnosis in trauma patients (area under the curve [AUC] 0.8939, 95% CI 0.8326 to 0.9552), which was superior to d-dimer (AUC 0.5881). The Hepatic Procoagulant Index combined plasma levels of PS + HMPs and albumin, increasing the AUC to 0.8978 (95% CI 0.8396 to 0.9561). This is the first study that addressed circulating PS + HMPs are promising biomarkers with high performance in diagnosing DVT. The Hepatic Procoagulant Index is a potential predictor of DVT in trauma patients.